2020
DOI: 10.1532/hsf.3029
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Discharged Loop Diuretic Dose to Home Dose on Hospital Readmissions in Patients with Acute Decompensated Heart Failure: A Retrospective Cohort Study

Abstract: Background: Acute decompensated heart failure (ADHF) is associated with a high rate of hospital readmission. The aim of this study is to examine the effect of the discharge diuretic dose compared with the home diuretic dose on hospital readmission in patients with ADHF. Methods: A single center retrospective cohort study included patients with a confirmed diagnosis of ADHF with an ejection fraction of less than 40%. The sample was divided in two groups. The first group received a total daily discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The findings of our study are quite interesting since the reported rate of hospital readmission in patients with a history of HFrEF in KSA can be as high as 37%. [ 36 ] Little is known about the effectiveness of sacubitril/valsartan in KSA, and the results of our study could have a meaningful impact on the current practice in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 98%
“…The findings of our study are quite interesting since the reported rate of hospital readmission in patients with a history of HFrEF in KSA can be as high as 37%. [ 36 ] Little is known about the effectiveness of sacubitril/valsartan in KSA, and the results of our study could have a meaningful impact on the current practice in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 98%
“…Despite dramatic improvements in treatment outcomes, hospital readmissions related to exacerbation of HF remain high in many countries. The evidence revealed that all-cause 30-day readmissions due to HF exacerbation in Saudi Arabia can be as high as 37% ( Alshibani et al, 2020a , Alshibani et al, 2020b ). In 2012, the national all-cause 30-day readmission rate after HF admission in the U.S. and Canada was more than 20% ( Measure update and specifications, 2014 , Canadian Institute for Health Information.…”
Section: Introductionmentioning
confidence: 99%